RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN - MOHAMMAD SOFYAN (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2019)
Financial Report is anoverview of the company's financial condition at any given moment. The instrument usedfor the analysis of financial condition as follows: Balance Sheet and Income Statement.The aim is to assess the financial performance of Generali Indonesia life insurance. From the analysis of the ratioof annual financial report Generali Indonesia life insurance illustrate that any analysis of 2012-2017 the ratio is still below theindustry standard ratio. This resulted in financial performance has not been good.